Efektivitas Pelatihan “Goting” Untuk Meningkatkan Kemandirian Belajar Siswa SMP - PRAPTI MADYO RATRI; Wiwien Dinar Pratisti; Zahrotul Uyun (Universitas Islam Indonesia, 2021)
This research aims to examine the impact of “Goting” training in increasing the learning independence of junior high school students. A total number of 14 students who had a medium score of learning independence participated in this study. They have assigned into two groups, with seven students as the experimental group and seven students as the control group. The experimental group has given “Goting” training while the control group was a waiting list group. This study uses a learning independence scale (52 items) which refers to Song & Hill (2007) aspects, namely Personal Attributes, Processes, and Learning Context. The result of this study showed that there is a significant effect between the experimental group and the control group.